Leveraging Virtual Learning Environments for Training Interpreter Trainers - Moser-Mercer, Barbara; Class, Barbara; Seeber, Kilian (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractWhile the demand for conference interpreters in traditional language combinations (the more widely used languages) is decreasing, the need for experts in less widely used languages is rapidly increasing with each enlargement of the EU. Post-war peace-keeping operations as well as warcrime tribunals have also increased the need for high-level interpreters in languages hitherto not used in the international arena and consequently more well-trained interpreter trainers both for traditional programs as well as ad-hoc intensive programs must be available. Interpreters are a highly mobile community of professionals, unable to be physically present in a university for long periods of time to be trained as trainers. The Certificate course for Interpreter Trainers at ETI (University of Geneva) has been offering the only postgraduate course for training interpreter trainers since 1996. To meet the demand for training around the world the Certificate course is now offered in a blended format: Nine months of distance learning are blended with one week of faceto-face learning. The portal (www.unige.ch/eti/certificate/training) offers a rich learning environment with a number of tools to implement the philosophy of collaborative learning. With its public access and a special section for students of interpreting the portal has become an international meeting point for interpreter trainers where participants in the Certificate course interact with interpreting students at ETI, and interpreter trainers from schools around the world can interact with the Certificate teaching staff and students. This paper reports on the first systematic assessment of both the learning environment and the learning outcomes of the Certificate course.